PENDAMPINGAN DAN PENGEMBANGAN UMKM WARUNG PONDOK PESONA SEBAGAI UPAYA UNTUK MENINGKATKAN EKONOMI KELUARGA - Yana Fajar Raihan; Moh. Fathkul Anam; Aril Dwi Rangga Ardiyansah; Adelia Ika Damayanti (LPPM AN Nuur, 2025)
Background: Micro, Small, and Medium Enterprises, or MSMEs, play a crucial role in driving the Indonesian economy. There are 64.2 million MSMEs operating and employing 97% of the national workforce (Ministry of Cooperatives and SMEs 2018). However, many MSMEs still face challenges and challenges in managing their businesses. One of the MSMEs, namely the MSME